2014
DOI: 10.5860/crl13-408
|View full text |Cite
|
Sign up to set email alerts
|

A Usability Evaluation of Academic Virtual Reference Services

Abstract: This study examined the usability of five virtual reference services-instant messenger chat, e-mail, telephone, text messaging, and Skype videoconferencing-by having 31 undergraduate and graduate students evaluate the usability of the virtual reference services of two different universities. The study's results suggest that user preference and satisfaction for virtual reference service are highly correlated with the service's overall usability in terms of effectiveness and efficiency. Online chat was rated hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…Steiner (2011) writes that physical reference service remains the best option for those who feel their questions are too nebulous for quick answers or who prefer the familiarity of working with a known and trusted librarian. Participants in the study of Chow and Croxton (2014) appeared to prefer the specific type of reference medium that most conveniently met their needs at any given time. Connaway and Radford (2011) suggested that VRS allows libraries to offer an alternative that may be important to students who find faceto-face interactions intimidating.…”
Section: Face-to-face Reference Services: Librarians' Point Of Viewmentioning
confidence: 96%
See 1 more Smart Citation
“…Steiner (2011) writes that physical reference service remains the best option for those who feel their questions are too nebulous for quick answers or who prefer the familiarity of working with a known and trusted librarian. Participants in the study of Chow and Croxton (2014) appeared to prefer the specific type of reference medium that most conveniently met their needs at any given time. Connaway and Radford (2011) suggested that VRS allows libraries to offer an alternative that may be important to students who find faceto-face interactions intimidating.…”
Section: Face-to-face Reference Services: Librarians' Point Of Viewmentioning
confidence: 96%
“…Chow and Croxton (2014) found that online chat was rated highest in effectiveness, efficiency, and satisfaction among VR services. One reason for this was because transactions were faster using chat in comparison to all other services.…”
Section: Answers In Vrsmentioning
confidence: 97%
“…Surveys analyze usage of increasing numbers of technologies including email and chat (Dee & Allen, 2006); email, chat, and phone (Mon et al, 2008); email-only reference, synchronous reference, and no virtual reference (Mu et al, 2011);email, chat, and text (Dorris et al, 2009); email, reference forms, forums, video conferencing, and chat (Bao, 2003); and finally email, chat, text, and video conferencing (Chow & Croxton, 2014). Clearly virtual reference services are popular but none of the studies above are conducted on a large scale.…”
Section: Types Of Virtual Reference Servicesmentioning
confidence: 98%
“…These studies ask how users discover reference services on libraries' websites with particular attention to the placement of the link to services on libraries' websites (Chow & Croxton, 2014;Dee & Allen, 2006;Mu, Dimitroff, Jordan, & Burclaff, 2011). Bao (2003) reports only 52% of the libraries in the sample presented web-based interactive reference services on their homepages.…”
Section: How Do Users Discover Virtual Reference?mentioning
confidence: 99%
“…that online chat reference is suitable mostly for simple factual and directional but not reference questions." 11 Cabaniss's analysis discovered that at the University of Washington Libraries, the majority of questions consisted of general information and known-item searches, queries that could be answered by graduate student assistants. 12 However, other studies mention the extent to which instruction is taking place within the chat environment, suggesting that, in many cases, the service moves beyond simply answering factual questions and provides an experience to users that allows them to develop new skills.…”
Section: Research Questions Research Sub-questionsmentioning
confidence: 99%